PERBANDINGAN EFISIENSI ENERGI DAN BIAYA PADA KOMPOR INDUKSI TERHADAP KOMPOR LISTRIK DAN KOMPOR GAS - Aas Wasri Hasanah; Oktaria Handayani (Sutet, 2016)
The stove is cooking tool that can generate high heat and the household items that have become a major necessity for every human being. Leaving aside the traditional stove that has been rarely used in Indonesia, there are several types of stoves based on a source of heat that is used at present, namely a gas stove (using gas), electric cooker (using current litrik) and induction cookers (using an electric current). After testing to determine the efficiency and heating costs by as much as 1liter water until it reaches its boiling temperature, showed that the induction hob (1200W) have high efficiency and better cost than gas stove that is equal (74.03% / 38.55%), (Rp152,56 / US $ 161.25). Similarly, when compared with electric stove at the same great power 600W, induction cooker efficiency and better cost anyway, namely (67.24% / 56.29%), (Rp167,93 / US $ 200.64). In terms of security, the induction cooker has a security level that is very nice and friendly to the environment when compared with a gas stove that many lead to fires and even explosions if the wrong in the procedure user and to the type of electric stoves also have a level of security as well as the induction cooker, but requires delay time to preheat so it takes a long time for the heating process. From these test results it can be said that the induction cooker is better when compared to other types of stoves.